Environmental Literacy Skills Based on Gender and Accreditation Among High School Students in Batu City - Pratama, Diaz Candra; Rahardjanto, Abdulkadir; Husamah, H. (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
The increasing environmental challenges faced globally have highlighted the urgent need for an environmentally literate generation. Environmental literacy, encompassing cognitive, affective, and behavioral aspects, is essential for fostering awareness and concern for the environment among young people. As such, understanding the level of environmental literacy in students is crucial to effectively address these challenges. This study aims to determine the environmental literacy skills of high school students in Batu City based on gender and school accreditation. The study used a descriptive quantitative approach with a purposive sampling technique. The research sample consisted of 1,054 students from six high schools, including three public schools and three private schools. The instrument used was a validated Environmental Literacy Instrument for Students (ELIS) based on a questionnaire. The results indicated that, in general, students' environmental literacy skills were in the high category, with an average percentage of 78-80% across all dimensions. The Independent sampel t-test revealed a significant difference in environmental literacy skills based on gender, with female students demonstrating higher concern for the environment compared to male students. Additionally, a significant difference was found between schools with A and B accreditation, with A-accredited schools showing higher results. This study recommends emphasizing the importance of experiential learning, as well as considering gender and accreditation factors in the development of environmental literacy programs.